On the U-WPF Acts over Monoids - A. Golchin (Journal of Sciences, Islamic Republic of Iran)
Valdis Laan in [5] introduced an extension of strong flatness which is called weak pullback flatness. In this paper we introduce a new property of acts over monoids, called U-WPF which is an extension of weak pullback flatness and give a classification of monoids by this property of their acts and also a classification of monoids when this property of acts implies others. We also show that regularity and strong faithfulness of acts both imply U-WPF. An equivalent of that over monoids for which torsion freeness implies U-WPF is given too.